Physical and Thermal Properties of Briquettes from Empty Fruit Bunches and Palm Kernel Shell by Mixing Tapioca Flour and Molasses - Tintan Rostina; Sri Suryaningsih (Universitas Padjadjaran, 2021)
West Java has the potential of palm oil wastes such as empty fruit bunches (EFB) and palm kernel shell (PKS) that can be used for fabrication of briquettes as raw materials. Briquette as a solid fuel and as a substitute for fossil fuel must have a good quality to be accepted in the market, such as having a good thermal and good physical properties. This research, reviewing the effect of particle size parameter and the effect of adding adhesive on briquette to heating value, thermal properties and physical properties. Briquettes were determined by using varying EFB and PKS biomass ratios of 50:50 and by adding 7% adhesive from tapioca flour or molasses of the total mass of the briquette. Particle size variations are set for 20 mesh and 40 mesh. The best heating value was found at 5,898 cal/g in the sample briquette by using 40 mesh particle and tapioca flour adhesive. The thermal properties test shown the combustion rate of 0.34 g/minutes and combustion lenght of 111 minutes found in 40 mesh briquette sample by using tapioca flour adhesive. The physical properties test shown the best density value of 0.215 g/cm3 and shattering resistance of 66,23% found in the 40 mesh briquette sample by using tapioca flour adhesive. The best durable value found in sample briquette with 20 mesh particle with tapioca flour adhesive which is 54.35%. The result was indicated that briquette with 40 mesh particle size and tapioca flour adhesive gives the best result of heating value, thermal properties and physical properties.Keywords: briquette, palm oil, thermal properties, physical properties, tapioca, molasses.